2023
DOI: 10.1039/d3ob00198a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of fused quinazolinones via visible light induced cyclization of 2-aminobenzaldehydes with tetrahydroisoquinolines

Abstract: This study reports a novel method for the synthesis of fused quinazolinone by the visible-light-induced cyclization of 2-aminobenzaldehyde and tetrahydroisoquinoline. The reaction was carried out under different experimental conditions and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Jiangxi Province Key Laboratory of Synthetic Chemistry, East China University of Technology, Nanchang, 330013, China. E-mail: zbxie@ecut.edu.cn visible light has a wide range of practical applications in the fields of organic synthetic chemistry [36][37][38][39][40][41] and photocatalytic composite materials. 42,43 Inspired by recent photochemical studies, we report a new approach for the green synthesis of quinazolinones using benzyl bromide and 2-aminobenzamide under mild conditions without additives, oxidants, or catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiangxi Province Key Laboratory of Synthetic Chemistry, East China University of Technology, Nanchang, 330013, China. E-mail: zbxie@ecut.edu.cn visible light has a wide range of practical applications in the fields of organic synthetic chemistry [36][37][38][39][40][41] and photocatalytic composite materials. 42,43 Inspired by recent photochemical studies, we report a new approach for the green synthesis of quinazolinones using benzyl bromide and 2-aminobenzamide under mild conditions without additives, oxidants, or catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, visible light has been successfully utilized as a clean energy source with high sustainability and environmental friendliness. Researchers have found that visible light has a wide range of practical applications in the fields of organic synthetic chemistry 36–41 and photocatalytic composite materials. 42,43 Inspired by recent photochemical studies, we report a new approach for the green synthesis of quinazolinones using benzyl bromide and 2-aminobenzamide under mild conditions without additives, oxidants, or catalysts.…”
Section: Introductionmentioning
confidence: 99%